Exploring trends in e-business and sustainable finance: an integrated analytical approach - Ahmad, Vasim; Arora, Madhu; Sayal, Anu; Kumar, Rakesh; Kumar, Pawan (Frontiers in Sustainable Cities, 2025)
IntroductionThis study explores two decades’ worth of developments and trends in e-business as also in sustainable finance. Despite a vast amount of research on e-business, its overlap with sustainable finance is not vast, which makes a study on the trends as also on digital business models’ relevance with drivers of sustainability necessary.MethodsBibliometric analysis is also adopted in the research in order to study global publication trends, citation networks, as well as key contributors in e-business as well as in sustainable finance. The research employs a vast data collection gathered from Scopus that investigates over 459 research studies between 2000 and 2024. The Analytic Hierarchy Process (AHP) is also adopted in order to rank drivers that have been identified from a vast literature review.ResultsResults indicate that the USA, UK, and China are leading in terms of publication as well as authoring. Social sustainability is seen as prioritized followed by technological sustainability, with least prioritized as governance sustainability. AI, blockchain, and IoT have been identified as drivers in e-business as well as finance as a means towards technological advancement.DiscussionIntegrating e-business with sustainable finance holds high promise for innovative, sustainable finance solutions. The study calls for more empirical studies with structural equation models and other decision models that can be adopted in order to foster digital business model sustainability. The study also brings into perspective digital strategy convergence with sustainability challenges in order to enhance growth in the long term.